Strategi Peritel Lokal Daerah Pasca Masuknya Peritel Lokal Nasional dan Peritel Asing - Khusniyah Purwani (Jurnal Aplikasi Bisnis, 2017)
This article describes the conditions of local retailers after the penetration of national retailers and foreign retailers. A local retailers is one of emergence originates from a local area. The form of their enterprise changes from the former conventional or traditional shops into local retailers which are managed according to modem standard with its "self service" concept after the penetration of national orforeign retailers. Several main factors that play important roles in the development of local retailers include capital resources, human resources, demographic characteristic, regulation, designs, merchandise and promotion. Think regionally and act locally strategy can be used to maintain consumers of local retailers.